Análise da cadeia produtiva do arroz beneficiado no município de Itaqui-RS: identificando seus destinos - (:unkn) unknown (Universidade Federal do Pampa, 2014)
In the municipality of Itaqui agricultural production of rice is quite intense, assuming a prominent position in the regional scenario. However, to ensure the quality of these grains and competitiveness of products, factors such as storage, processing and transportation are key as infrastructure deficiencies can substantially reduce the competitive potential of these products in the Brazilian agribusiness. In this scenario, this paper analyzes the system of logistics, warehousing and shipping of grain harvest , identifying marketing channels adopted by rice processing companies in the municipality of Itaqui, identifying the main destinations of the product and the critical points highlighted by marketing organizations. To do so, through a case study , a survey was conducted on grain production in the database of the Brazilian Institute of Geography and Statistics (IBGE) , Rio Grandense Rice Institute (IRGA) , Rural Union and Itaqui Maçambará, and research the field with four processing companies and also in the National Supply Company (Conab). As a result, it was found that rice Long Slim Type 1 is the most processed and marketed, and its main target is the Southeast, already the most used marketing channels are level one and level two. Finally , it is noteworthy that the distribution is done through road and the prospects of jail for the future is promising for meeting the rapidly developing .
Keywords: Indústrias de arroz; Canais de comercialização; Logística; Rice industries; Marketing; Logistics channels; CNPQ::CIENCIAS AGRARIAS